How to Organize Literature and Notes in Zotero (How to do X in Linguistics 13) (Computer-Assisted Language Comparison in Practice: Tutorials on Computational Approaches to the History and Diversity of Languages, 2023)
Reading, summarizing, and citing literature is an essential part of every student and researcher’s life. While there are many books and workshops on academic writing, there is less information on how to efficiently organize literature. For this reason, I offer an overview of how to organize literature and notes in Zotero. Specifically, I illustrate some of my own workflows for organizing the literature for my dissertation. I also discuss general features of Zotero. The interested reader who wants to learn more will benefit from the related links.
Keywords: Zotero; todo list; organization; tutorial